The role of ICG-fluorescence imaging in abdominal surgical oncology - V. Yu. Dubrovin; S. S. Tymchuk; V. V. Davletshina; R. V. Pavlov; V. A. Kashchenko (Сибирский онкологический журнал)
The purpose of the study was to summarize and analyze the available data on modern methods of additional imaging using indocyanine green (ICG) used in abdominal surgical oncology.Material and Methods. The search and analysis of publications over the last 7–10 years was carried out using RSCI (Russian Science Citation Index), E-library, PubMed, Scopus, MedLine, Elsevier, Web of Science, ScienceDirect systems. The following keywords were used for the search: “ICG-fluorescent navigation”, “ICG-fluorescence”, “gastric cancer”, “colorectal cancer”, “indocyanine green”.Results. The role of ICG-fluorescent navigation in abdominal oncology, in particular, in surgery for cancer of the stomach, colon and rectum, identification of peritoneal carcinomatosis and liver metastases, as well as in biliary surgery and cholangiography, was shown. Intraoperative visualization of sentinel lymph nodes and mapping of lymph nodes in patients with gastric and colorectal cancers were described. In addition, the information on the diagnostic value of vascular imaging in colorectal surgery, detection of the boundaries of hepatocellular carcinoma and surrounding tissues, as well as real-time liver metastases using indocyanine green, was provided. Special attention was paid to ICG-mediated cholecystectomy and cholangiography. ICG fluorescence imaging in colorectal and gastric cancer surgery makes it possible to individualize the surgical approach and provide functional surgery associated with the performance of a sufficient and prophylactically excessive volume of surgical intervention more effectively. Conclusion. The presented data confirm the relevance of the search for a vector of improving the imaging methods used in abdominal surgical oncology, which requires even more even more multicenter prospective cohort studies to determine the best ways of improving the technique.